Settling Accounts at the End of History: A Nonideal Approach to State Apologies - Friedrich, Jasper (Political theory, 2022)
What are we to make of the fact that world leaders, such as Canada’s Justin Trudeau, have, within the last few decades, offered official apologies for a whole host of past injustices? Scholars have largely dealt with this phenomenon as a moral question, seeing in these expressions of contrition a radical disruption of contemporary neoliberal individualism, a promise of a more humane world. Focusing on Canadian apology politics, this essay instead proposes a nonideal approach to state apologies, sidestepping questions of what they ought to do and focusing instead on their actual functioning as political acts. Through a sociologically informed speech act theory and Foucault’s work on power, apology is conceptualized as a speech act with an essentially relational nature. The state, through apologizing, reaffirms the norms governing its relationship to its subjects at a moment when a past transgression threatens to destabilize this relation. From a Foucauldian point of view, the state’s power inheres in the very stability of the state–citizen relation, and we should therefore see apologies as defensive moves to protect state hegemony. In the context of Western liberal democracies, such as Canada, apologies embody, rather than challenge, the logic of neoliberal governmentality by suggesting that everything, including resentment against the state, can be managed within the current status quo. Nevertheless, total cynicism about apology politics is not warranted. In many indigenous apology campaigners’ demands for contrition we see another side of apologies: their potential to bring about change by enacting counterhegemonic relations to the state.